2017
DOI: 10.1002/pc.24581
|View full text |Cite
|
Sign up to set email alerts
|

Improving mechanical, thermal, and electrical properties of polyimide by incorporating vinyltriethoxysilane functionalized graphene oxide

Abstract: Functionalized graphene oxide (FGO) nanosheets were produced by reacting graphene oxide with vinyltriethoxysilane (VTES). The vinyltriethoxysilane graphene oxide and polyimide (VGO/PI) composites were prepared by solution blending method. In comparison with the pristine polyimide (PI) and graphene oxide/polyimide (GO/PI) composite, VGO showed better mechanical, electrical and thermal properties. The tensile strength of VGO/PI composite with 0.8 wt% VGO loading was up to 148 MPa, i.e., 105% higher than that of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…The results indicate that the electric conductivities of the composites depended on the electric properties of the polymer chain. It has been reported that GO is considered as a nonconductive material 12 . The lower σ value of GO‐AP‐PAN/PANPrSO 3 H corresponds to the low content of self‐doped PANPrSO 3 H unit in the composite.…”
Section: Resultsmentioning
confidence: 99%
“…The results indicate that the electric conductivities of the composites depended on the electric properties of the polymer chain. It has been reported that GO is considered as a nonconductive material 12 . The lower σ value of GO‐AP‐PAN/PANPrSO 3 H corresponds to the low content of self‐doped PANPrSO 3 H unit in the composite.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the strength and modulus of the single-layer PI-Mica film are superior to those of other PI-based composite films (Figure 2e and Table S1, Supporting Information). [15,28,[31][32][33][34][35][36][37][38][39][40][41] The improvement in the mechanical properties of the final singlelayer PI-Mica film is mainly attributed to its ordered and uniform layered microstructure. [42,43] However, we found that after tensile failure in single-layer PI-Mica films, many of the mica nanosheets were pulled out from the PI matrix at the fracture location, forming prominent trapezoidal structures and irregular deflections (Figure S4b-f, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…The improvement in mechanical properties can be primarily ascribed to the homogeneous dispersibility of Gr-PANI 10:1 in PI matrix because of the “non-covalent welding” strategy. 39 …”
Section: Resultsmentioning
confidence: 99%